Hak Waris Janda Talak Bāin oleh Suami yang Sakit Parah Menurut Imam Malik dan Imam Syafii serta Implementasinya dalam Kompilasi Hukum Islam - Yuli Yuli; Mukran H. Usman; Sirajuddin Sirajuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the inheritance rights of wives who are divorced by husbands who are seriously ill according to the views of Imam Malik and Imam Syafii and their application in the Compilation of Islamic Law (KHI). This research is a library research, using a normative approach and a comparative approach. The results of the study found that there were differences of opinion between Imam Malik and Imam Syafii regarding the inheritance rights of wives who were divorced by husbands who were seriously ill. according to the rules of saddu al-żarī'ah, closing loopholes for husbands who reject their wives with the intention that the wife does not receive an inheritance. These two opinions will be the same when viewed from the KHI's point of view, because divorce from the KHI's point of view is the process of pronouncing a divorce vow which must be carried out in front of the court and witnessed by the judge of the Religious Court. If the pronouncement of the divorce pledge is made outside the courtroom, then the divorce is considered invalid and does not have binding legal force. Article 137 KHI also states that a divorce suit is void if the husband and wife die before the decision of the Religious Court regarding the divorce suit is made.